Novelties in Brazilian Anchietea A.St.-Hil. (Violaceae): A new species from inselbergs in the Atlantic rainforest and an update on the conservation status of Anchietea ferrucciae Paula-Souza & Zmarzty - de Paula-Souza, Juliana; Pirani, José Rubens (Phytotaxa, 2016)
Anchietea ballardii Paula-Souza, a new species of Violaceae endemic to inselbergs in Espírito Santo state, Brazil, is described and illustrated. The new species is morphologically similar to Anchietea ferrucciae Paula-Souza & Zmarzty, endemic to the Caatinga in Bahia state, being recognized by its obovate to suborbicular fruit valves, ovate or widely elliptic to suborbicular leaves and more congested arrangement of leaves and flowers/fruits. An updated key to the species of Anchietea A.St.-Hil. is provided, and a preliminary conservation assessment using IUCN criteria are provided for both the new species and and A. ferrucciae. Anchietea ballardii Paula-Souza, uma nova espécie de Violaceae endêmica de inselbergs do Espírito Santo, Brasil, é descrita e ilustrada. A nova espécie é morfologicamente relacionada à Anchietea ferrucciae Paula-Souza & Zmarzty, endêmica da Caatinga da Bahia, sendo distinta pelas valvas dos frutos obovais a suborbiculares, folhas ovais ou largamente elípticas a suborbiculares e arranjo mais congesto de folhas e flores/frutos. Uma chave de identificação atualizada para as espécies de Anchietea A.St.-Hil. é apresentada, assim como a avaliação de seu status de conservação e o de A. ferrucciae.